Dynamics of Interdisciplinary Islamic Education Learning in Indonesian High Schools Based on Islamic Law - Masdin, Masdin; Ilham, Muhammad; Mulu, Beti; Nurfaidah, Sitti; Samrin, Samrin (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
Twenty-first-century learning demands that students go beyond mastering religious content to solve authentic problems collaboratively. Islamic Religious Education must adopt an interdisciplinary approach rooted in Islamic law that bridges Qurʾan–Sunnah teachings with social sciences, science, technology, arts, and culture. This study aims to reveal the essence of the experiences of Islamic Religious Education teachers in Kendari senior high schools who have integrated Islamic Religious Education content with other disciplines for at least one year. A qualitative phenomenological design was employed. Purposefully selected teachers participated in in-depth interviews, participatory observations, and written reflections. Data were analyzed through bracketing, phenomenological reduction, textural-structural description, and synthesis of the essence following the Moustakas model. Findings confirm that an interdisciplinary, law-based Islamic Religious Education framework cultivates a contextual and collaborative learning ecosystem. The study affirms that an interdisciplinary approach grounded in Islamic law enhances student learning quality and continuously builds teacher competence, collaboration, and self-reflection, fostering a more adaptive and innovative school ecosystem aligned with Islamic character values by designing maqasid-based